Diferença na representação do gaúcho em Martín Ferro, O vaqueano e Um certo Capitão Rodrigo - Cazzonato, Milena Taliza (2024)
The present study emphasizes the importance of historical and literary knowledge for valuing the cultural identity of a social type. The research, carried out within the scope of the Postgraduate Program in Literature at the University of Passo Fundo, addresses the representations of the gaucho in literature, analyzing the works Martín Fierro (1872) by José Hernández, O vaqueano (1872) by Apolinário Porto Alegre and A certain Cap. Rodrigo (1949) by Erico Verissimo. By investigating the tensions between these representations, the research contributes to a broader understanding of the identity construction of southern Latin American men over the centuries. This dissertation, inserted in the research line "Production and reception of literary texts" at PPGL/UPF, adopts a qualitative and bibliographic methodology to analyze the selected works and seeks to identify the intrinsic characteristics of the gaucho in literature. It uses as its main theoretical basis the studies of Antônio Candido, on the construction of the character, Tânia Franco Carvalhal, related to comparative literature, Stuart Hall, referring to the theory of representation and identity. With an explanatory approach, the study intends to analyze the factors of proximity and distance of the figure of the gaucho in literature, considering aspects such as behavior, reality and representation. Organized into five chapters, the dissertation presents a detailed analysis of the selected works, highlighting biographical aspects of the authors, plot and behavior of the characters, in addition to a comparative study between the representational differences of the characters presented. Therefore, through this research, we seek to contribute to the advancement of knowledge related to the representation of the gaucho / gaucho in literature, providing a comprehensive view of the different conceptions of the gaucho over time and geographic space.